Working to be someone : child focused research and practice with working children - Hungerland, Beatrice, 1962- (Jessica Kingsley, 2007)
Presents an overview of worldwide research on working children that takes the children's own points of view of their work into account. This book aims to highlight and discuss children's employment from a point of view that amplifies their concern rather than disengaging them from adult constructed arguments.